Key to species of the leafhopper genus Fistulatus Zhang, Zhang & Chen (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with description of a new species - Hassan, Muhammad Asghar; Shah, Bismillah; Xing, Jichun (Zootaxa, 2024)
A new leafhopper species: Fistulatus motuoensis Hassan & Xing sp. nov. is described and illustrated from Xizang Autonomous Region, China. A key based on the aedeagus is given to distinguish all species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).